Effects of habitat fragmentation on the reproductive ecology and conservation genetics of the almendro (Dipteryx panamensis), a keystone rainforest tree - Hanson, Thor (2006)
Tesis (Ph. D.) -- CATIE. Escuela de Posgrado, Turrialba (Costa Rica), University of Idaho